Self-Assembled Colloidal Photonic Crystal on the Fiber Optic Tip as a Sensing Probe - Pasquale Di Palma; Chiara Taddei; Anna Borriello; Giovanna De Luca; Michele Giordano; Agostino Iadicicco; Stefania Campopiano; Lucia Sansone (IEEE Photonics Journal)
This paper presents an effective and efficient method to fabricate novel fiber optic sensing probes. The new, simple, and low cost approach is based on a 3-D photonic crystal dielectric structure directly deposited on the tip of a multimode optical fiber through the self-assembly of colloidal crystals (CCs) via a vertical deposition technique. Here, the CC is made of polystyrene nanospheres with 200 nm diameter, and the optical fiber is a UV–vis fiber with a core diameter of 200 μm. The obtained fiber probes exhibit a resonant peak at 480 nm and an amplitude enhancement of 3.7 with respect to the bare fiber; these results are highly repeatable. A numerical tool based on a finite element method analysis has been developed to study and analyze the 3-D subwavelength structures. Numerical results are in good agreement with the observed experimental spectra. Moreover, refractive index measurements have been carried out, revealing a sensitivity of up to 445 nm/RIU in the 1.33–1.36 values range. The achieved performances, which have been obtained by using very small active areas and an easy and reliable fabrication procedure, demonstrate the future perspectives of these fiber-optic probes for chemical and biological sensing applications.